CAUSE FACTORS OF JUVENILE DELINQUENCY SYMPTOMS IN CLASS VII SMP DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2019/2020 - I MADE PURANA; JOVIN ARISTO ANA RATO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Juvenile delinquency at school age who should be studying at school turns out to be some of them doing things that are not commendable. Juvenile delinquency at school age is very troubling, generally parents, and the general public. Therefore, teenagers should get special attention from parents when they are at home and by teachers at school. The formulation of the problem was the factors that cause the symptoms of juvenile delinquency at SMP Dwijendra Denpasar in the academic year 2019/2020. What efforts are being made to prevent juvenile delinquency at SMP Dwijendra Denpasar in the academic year 2019/2020? The purpose of the research was to determine the factors causing the symptoms of juvenile delinquency at SMP Dwijendra Denpasar in the academic year 2019/2020. To find out what efforts are being made to prevent juvenile delinquency at SMP Dwijendra Denpasar for the academic year 2019/2020. The technique used to collect data in this research was the technique of observation, interviews, library studies, documentation. The data analysis used in this research was a qualitative descriptive analysis. The results of the research treat (1) The factors causing the symptoms of juvenile delinquency at SMP Dwijendra Denpasar in the academic year 2019/2020 were family factors, especially parents. In this case it is parents who do not understand the meaning of children's education, and who are so busy working. Inharmonious marital relationship. Environmental factors, school factors, including teachers, lessons, school assignments and others related to school. (2). The efforts to prevent juvenile delinquency in SMP Dwijendra were eliminating all causes of juvenile crime, whether personal, familial, socio-economic and cultural. Making changes to the environment by good communication with adoptive or foster parents and providing the necessary facilities for healthy physical and spiritual development for adolescent.